Presenting a Model of Factors Affecting the External Financing of Innovation in Small and Medium Enterprises Using the Meta-Synthesis Method - Hooman Shababi (سیاست نامه علم و فناوری, 2022)
The purpose of this study is to identify the factors affecting external financing of innovation in small and medium enterprises by in-depth study of the research background and provide a model for it. An in-depth study of 257 articles, books and dissertations from reputable internal and external sources, meta-synthesis method and MAXQDA 10.0 qualitative analysis software were used, and the results showed that external and internal factors affect the external financing of innovation of small and medium enterprises. In the category of intra-organizational factors, technical and structural factors, human and political, and in the category of extra-organizational factors, legal, political and infrastructural factors affect the external financing of innovation of small and medium enterprises. Finally, a model of the factors affecting the external financing of innovation was presented. The current results could be a beacon for small and medium sized companies in external financing of innovation.